A psychosocial study of identity in selected novels of Ballard and Thompson - Modarresi, Mona (2013)
In the present globalized and fast-changing world, identity is among the most popularly studied constructs in social science. Focusing on context specific ways by which people act and speak is crucial in order to arrive at a dynamic social and psychological approach for recognizing identities. Within the social psychology discipline, Social Identity Theory has always been applied to clarify new dimensions of the different groups of people which form a society. These dimensions work toward distinguishing groups which are isolated, and seek to create and present their identity as being distinctive from that of members of a society who have conformed to the conditions of the time and are deemed acceptable by others. In other words, such dimensions result in distinguishing the “in-groups” from “out-groups”. It is the representation of the lives of such a group of people who are isolated in society, and who seek to define their identity in a specific way, that forms the subject of the two novels which are the basis of this study. One of the novels, Crash (1973), written by J.G. Ballard, describes the lives of a group of strange people living in London. These people, who had, at some point in their lives, been involved in at least one car accident, have subsequently become preoccupied with the idea that a car crash and the death that follows, possess the potential to unlock the key to “a new true identity”; which is perceived by the individual as being the permanent real life. The second novel discussed in this study, Fear and Loathing in Las Vegas (1998), written by Hunter S. Thompson, depicts the lives of two friends who head to Las Vegas, to cover a motor race report but in fact they seek their American Dream. Both novels are basically representations of a group of people who attempt to escape the world that they live in, to search for a new identity. Through the analysis of the two stories based on the Social Identity Theory formulated by Henry Tajfel and John Turner (1979), the researcher is conducts a psychosocial study on the protagonists’ identities. In other words, application of this theory would help to explain how the major characters of the novels as individuals isolated from society undertake to define their identity, observe the society they live amidst and gain insight from.